Extracorporeal Shockwave Therapy Versus Kinesiology Taping in the Management of Plantar Fasciitis: A Randomized Clinical Trial - Banu ORDAHAN,; Gözde TÜRKOĞLU,; Ali Yavuz KARAHAN,; Halil Ekrem AKKURT, (Archives of Rheumatology, 2017)
Objectives: This study aims to compare the efficacy of extracorporeal shockwave therapy (ESWT) and kinesiology taping in the treatment of plantar fasciitis. Patients and methods: The study included 80 patients diagnosed with plantar fasciitis. The patients were randomized into two groups as ESWT (9 males, 28 females; mean age 47.8±12.4 years; range 40 to 55 years) and kinesiology taping (KT, 7 males, 26 females; mean age 47.7±9.8 years; range 40 to 55 years) groups. Groups were similar regarding age, sex, and body mass index (all p>0.05). Three patients in ESWT group and seven patients in KT group were lost to follow-up. ESWT was applied once a week for five weeks, while KT was applied every five days for five weeks. Patients’ pain and functional status were evaluated with visual analog scale, heel tenderness index, and foot and ankle outcome score before and after treatment. Results: At the study onset, there were no statistically significant differences between the two groups in their visual analog scale, heel tenderness index, and foot and ankle outcome scores. Five weeks later, both groups showed significant improvement in all parameters (p<0.05), but no significant differences were observed between the groups in the visual analog scale, heel tenderness index, and foot and ankle outcome score scores. Conclusion: Both ESWT and KT treatments improved pain levels and function and quality of life in individuals with plantar fasciitis. Neither method was superior in treating plantar fasciitis.